'Ultimate' Facts? Zalabardo on the Metaphysics of Truth. Issue 3 (3rd July 2018) - Floyd, Juliet
ABSTRACT: Zalabardo argues that the Tractatus account of picturing is a direct and successful refutation of Russell's 'multiple relation' theory of judgment, its role being ontological: Wittgenstein replaces objects in external relations with pictures. I argue instead that the idea of pictures as picturing possibilities of what is the case or not the case is fundamental to Wittgenstein's way of responding to the 'mode of combination' problem, and hence that modality is crucial to his response to Russell.